Automating monitoring and evaluation data analysis by using an open-source programming language - Nadia Fouché; Melody Mentz-Coetzee (African Evaluation Journal)
Background: African higher education institutions lag behind their global counterparts in the number of research outputs produced. To address this shortcoming, early-career researcher development programmes play a critical role. Monitoring and evaluation (ME) are vital in assuring that such programmes deliver meaningful outcomes. However, ME is an expensive process, which is problematic in the resource-constrained context of the African continent. Traditionally, practitioners use expensive data analysis software suites such as the Statistical Package for the Social Sciences (SPSS) for analysing quantitative ME data. Although open-source programming languages such as Python are free to use, there are no libraries in Python aimed at the analyses needed for quantitative ME data, resulting in a steep learning curve for new Python users.